Exploring public attitudes toward live-streaming fitness in China: A sentiment and content analysis of China's social media Weibo - Tian, Rui; Yin, Ruheng; Gan, Feng (Frontiers in Public Health, 2022)
Objectives: Live-streaming fitness is perceived by the Chinese government as an invaluable means to reduce the prevalence of physical inactivity amid the Covid-19 pandemic. This study aims to investigate the public altitudes of the Chinese people towards live-streaming fitness and provide future health communication strategies on the public promotion of live-streaming fitness accordingly. Methods: This study collected live-streaming fitness-related microblog posts from July 2021 to June 2022 in Weibo, the Chinese equivalent to Twitter. We used the BiLSTM-CNN model to carry out the sentiment analysis, and the structured topic modeling (STM) method to conduct content analysis. Results: This study extracted 114,397 live-streaming fitness-related Weibo posts. Over 80% of the Weibo posts were positive 229 during the period of the study, and over 85% were positive in half of the period. This study finds 8 topics through content analysis, which are fitness during quarantine; cost reduction; online community; celebrity effect; Industry; fitness injuries; live commerce and Zero Covid strategy. Conclusions: It is discovered that the public attitudes towards live-streaming fitness were largely positive. Topics related to celebrity effect (5% - 11%), fitness injuries (8% - 16%), live commerce (5% - 9%) and Zero Covid strategy (16% - 26%) showed upward trends in negative views of the Chinese people. Specific health communication strategy suggestions are given to target each of the negative topics.